2016
DOI: 10.17509/ijal.v5i2.1348
|View full text |Cite
|
Sign up to set email alerts
|

The use of Edmodo in teaching writing in a blended learning setting

Abstract: The advancement of technology provides education with varioussolutions to create new learning environments. Edmodo as a learning platform is believed to offera solution in the teaching of English, particularly for teaching writing. This research was aimed to investigate how Edmodo as a learning platform,in a blended learning setting, was implemented in teaching writing in its combination with Genre-based Approach, how Edmodo facilitated students’ engagement, and how students perceived the use of Edmodo in teac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
107
1
11

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(133 citation statements)
references
References 34 publications
14
107
1
11
Order By: Relevance
“…Similar findings are also reported by Nomass (2013), Golonka et al (2014), Parvin and Salam (2015), Hidayati (2016), and Gilakjani (2017). In the meantime, studies investigating the use of specific devices and platforms have also been reported including the use of WhatsApp (Alsaleem, 2014), Twitter (Clayton and Murphy, 2016), YouTube (Wang, Lai, and Wong, 2018), Edmodo (Purnawarman, Susilawati, and Sundayana, 2016), mobile phone (Stockwell, 2009), multimedia and language laboratory (Bachate, 2016), and Wiki technology (Lin and Yang, 2011).…”
Section: Introductionsupporting
confidence: 68%
“…Similar findings are also reported by Nomass (2013), Golonka et al (2014), Parvin and Salam (2015), Hidayati (2016), and Gilakjani (2017). In the meantime, studies investigating the use of specific devices and platforms have also been reported including the use of WhatsApp (Alsaleem, 2014), Twitter (Clayton and Murphy, 2016), YouTube (Wang, Lai, and Wong, 2018), Edmodo (Purnawarman, Susilawati, and Sundayana, 2016), mobile phone (Stockwell, 2009), multimedia and language laboratory (Bachate, 2016), and Wiki technology (Lin and Yang, 2011).…”
Section: Introductionsupporting
confidence: 68%
“…While in Indonesian context, Muhfidin (2013) states the use of Edmodo as the supplementary learning tool is effective and applicable for students. Furthermore, Edmodo also could be used in teaching writing in a blended learning setting since it facilitates students' engagement cognitively (Purnawarman et al, 2016).…”
Section: Information and Communication Technology (Ict) Has Been Intementioning
confidence: 99%
“…Some previous studies related to the role of Edmodo in learning were conducted by researchers, such as: Purnawarman, et al (2016), Yusuf, et al (2018), Al-Naibi et al (2018) are related. observed the effects of teaching writing English narrative text using Edmodo in blended learning and the result of their research revealed that there is an increasing result of the test before and after the treatment.…”
Section: A Introductionmentioning
confidence: 99%